2021
DOI: 10.3390/insects12030204
|View full text |Cite
|
Sign up to set email alerts
|

Chance or Necessity—The Fungi Co−Occurring with Formica polyctena Ants

Abstract: Studies on carton nesting ants and domatia−dwelling ants have shown that ant–fungi interactions may be much more common and widespread than previously thought. Until now, studies focused predominantly on parasitic and mutualistic fungi–ant interactions occurring mostly in the tropics, neglecting less−obvious interactions involving the fungi common in ants’ surroundings in temperate climates. In our study, we characterized the mycobiota of the surroundings of Formica polyctena ants by identifying nearly 600 fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…It is not known if Neocelosporium is associated with leaves of the mulga tree or with other plants likely to be in the vicinity of honeypot ant nests, or if it plays a role in the biology or nutrition of Camponotus , and these would be interesting areas for further study. The five remaining genera identified in the fungal microbiome all also have environmental niches in plants, water, and/or the soil suggesting that the honeypot ant fungal microbiome is largely obtained from foraging and environmental exposure ( Bizarria, Pagnocca & Rodrigues, 2022 ; Flakus et al, 2019 ; Siedlecki et al, 2021 ; Tsuneda et al, 2008 ). Unsurprisingly, the microbiome of HPAH was largely sterile and did not contain any yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known if Neocelosporium is associated with leaves of the mulga tree or with other plants likely to be in the vicinity of honeypot ant nests, or if it plays a role in the biology or nutrition of Camponotus , and these would be interesting areas for further study. The five remaining genera identified in the fungal microbiome all also have environmental niches in plants, water, and/or the soil suggesting that the honeypot ant fungal microbiome is largely obtained from foraging and environmental exposure ( Bizarria, Pagnocca & Rodrigues, 2022 ; Flakus et al, 2019 ; Siedlecki et al, 2021 ; Tsuneda et al, 2008 ). Unsurprisingly, the microbiome of HPAH was largely sterile and did not contain any yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…It was highlighted that meat tenderized with M. flavus has higher amounts of functional sweet-, savory-, and umami-tasting amino acids. Additionally, M. flavus is a fungus which naturally occurs on aged meat [ 14 , 27 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total genomic DNA was extracted from pure fungal culture on 4% SDA medium using DNA extraction kit EM13 (Blirt S.A., Gdańsk, Poland) according to the manufacturer’s instructions. The internal transcribed spacer (ITS) fragment was amplified and sequenced as described by Siedlecki et al [ 27 ]. Received sequences were compared with reference sequences deposited in GenBank database ( ).…”
Section: Methodsmentioning
confidence: 99%
“…Stingless bees have been shown to require sterols produced by a yeast associate to develop [33]. Schwanniomyces polymophus has been found associated with other ants and has also been shown to reduce complex oligosaccharides to simple sugars [20,62]. Fire ants have been reported to obtain ergosterol from associated yeast species [21].…”
Section: Discussionmentioning
confidence: 99%
“…(formerly Debaryomyces spp.) associated with the Formica rufa L., Formica aquilonia Yarrow, and Formica polyctena Foerst [16][17][18][19][20]. The relationship between Formica and this yeast remains unknown, but it was highlighted by these studies since the yeasts were found only in active ant colonies.…”
Section: Introductionmentioning
confidence: 99%